1985
DOI: 10.1104/pp.77.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Rhythms in Photosynthesis, Sucrose Phosphate Synthase Activity, and Stomatal Resistance in Leaves of Soybean (Glycine max [L.] Merr.)

Abstract: Experiments were conducted with soybean (Glycine max [L.] Merr. cv 'Ransom') plants to determine if diurnal rhythms in net carbon dioxide exchange rate (CER), stomatal resistance, and sucrose-phosphate synthase (SPS) activity persisted in constant environmental conditions (constant light, LL constant dark DD) and to assess the importance of these rhythms to the production of nonstructural carbohydrates (starch, sucrose, and hexose). Rhythms in CER, stomatal resistance, and SPS activity were observed in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 13 publications
1
46
0
2
Order By: Relevance
“…Flowers were the strongest sinks, since radioactivity in the soluble as well as in the insoluble fractions increased over time. These results were in accordance with data from soybean, showing that diurnal variation in storage was greatest in the leaf and decreased in the order leaf > petiole > stems > roots (Kerr et al 1985).…”
Section: Starchsupporting
confidence: 82%
“…Flowers were the strongest sinks, since radioactivity in the soluble as well as in the insoluble fractions increased over time. These results were in accordance with data from soybean, showing that diurnal variation in storage was greatest in the leaf and decreased in the order leaf > petiole > stems > roots (Kerr et al 1985).…”
Section: Starchsupporting
confidence: 82%
“…Our 1997 study showed that SPS activity exhibits diurnal and circadian rhythms in tomato, which are the result of corresponding oscillations in SPS protein phosphorylation state (Jones and Ort, 1997). To our knowledge, this was the first report of a circadian rhythm in SPS activity, although an endogenous ultradian rhythm with a period of about 12 h had been reported in soybean (Kerr et al, 1985). Our evidence indicates that the circadian rhythm in tomato SPS phosphorylation state is the result of circadian-regulated transcription of a protein phosphatase, possibly the one that dephosphorylates and thereby activates SPS.…”
mentioning
confidence: 85%
“…In fact, few proteins have been shown to have circadian oscillations in enzyme activity; those that have include NR (Lillo, 1984), SPS (Jones and Ort, 1997), and PEP carboxylase (Carter et al, 1991). Because circadian fluctuations are exhibited in many overt higher-plant processes, including leaf movement (Darwin, 1880;Satter and Galston, 1981), stomatal resistance (Martin and Meidner, 1971;Kerr et al, 1985;Holmes and Klein, 1986), and net photosynthesis (Chia-Looi and Cumming, 1972;Hennessey and Field, 1991), it seems unavoidable that many more enzymes must exhibit a circadian component to their regulation than the few so far identified. Circadian fluctuations in free cytosolic calcium (Johnson et al, 1995) may also play an important role in mediating the rhythms in these complex plant processes.…”
Section: Discussionmentioning
confidence: 99%
“…Rhythms in photosynthesis and in stomatal opening generally (but not always [10]) occur in synchrony, and are likely to be strongly interrelated. Stomatal opening is regulated by internal CO2 concentration, but it can also limit photosynthesis by limiting CO2 supply.…”
Section: Discussionmentioning
confidence: 99%